Combined chemotherapy with cisplatin, etoposide, and irinotecan versus topotecan alone as second-line treatment for patients with sensitive relapsed small-cell lung cancer (JCOG0605): a multicentre, open-label, randomised phase 3 trial. Issue 8 (August 2016) - Goto, Koichi; Ohe, Yuichiro; Shibata, Taro; Seto, Takashi; Takahashi, Toshiaki; Nakagawa, Kazuhiko; Tanaka, Hiroshi; Takeda, Koji; Nishio, Makoto; Mori, Kiyoshi; Satouchi, Miyako; Hida, Toyoaki; et al.
Summary: Background: Etoposide and irinotecan are key drugs in the treatment of small-cell lung cancer. We did this study to investigate whether combined chemotherapy with cisplatin, etoposide, and irinotecan was superior to topotecan monotherapy as second-line chemotherapy in patients with sensitive relapsed small-cell lung cancer. Methods: We did this open-label, multicentre, randomised phase 3 trial at 29 institutions in Japan. Patients with small-cell lung cancer that responded to first-line treatment but showed evidence of disease relapse or progression at least 90 days after completion of the first-line treatment were eligible to participate. Enrolled patients were randomly assigned (1:1) to receive combination chemotherapy with cisplatin plus etoposide plus irinotecan or topotecan alone. Randomisation was done via the minimisation method with biased-coin balancing for Eastern Cooperative Oncology Group performance status, disease stage at enrolment, and institution. Combination chemotherapy consisted of five 2-week courses of intravenous cisplatin 25 mg/m 2 on days 1 and 8, intravenous etoposide 60 mg/m 2 on days 1–3, and intravenous irinotecan 90 mg/m 2 on day 8, with granulocyte colony-stimulating factor given by hypodermic injection every day starting from day 9 of the first course (except on the days anticancer drugs were given). Topotecan therapy consisted of four courses of intravenous topotecan 1·0 mg/m 2 on days 1–5, every 3 weeks. The primary endpoint was overall survival in the intention-to-treat population, which was analysed with a one-sided α of 5%, and safety was assessed in all patients who received at least one dose of study drug. The trial is registered with University Hospital Medical Information Network Clinical Trials Registry, number UMIN000000828. Findings: Between Sept 20, 2007, and Nov 30, 2012, 180 patients were enrolled, with 90 assigned to each treatment group. The median follow-up for censored patients was 22·7 months (IQR 20·0–35·3). Overall survival was significantly longer in the combination chemotherapy group (median 18·2 months, 95% CI 15·7–20·6) than in the topotecan group (12·5 months, 10·8–14·9; hazard ratio 0·67, 90% CI 0·51–0·88; p=0·0079). The most common grade 3 or 4 adverse events were neutropenia (75 [83%] patients in the combination chemotherapy group vs 77 [86%] patients in the topotecan group), anaemia (76 [84%] vs 25 [28%]), and leucopenia (72 [80%] vs 46 [51%]). Grade 3 or 4 febrile neutropenia was more common in the combination chemotherapy group than in the topotecan group (28 [31%] vs six [7%]), as was grade 3 or 4 thrombocytopenia (37 [41%] vs 25 [28%]). Serious adverse events were reported in four (4%) patients in the topotecan group and nine (10%) in the combination chemotherapy group. Two treatment-related deaths (one each of pneumonitis and pulmonary infection) occurred in the topotecan group and one (febrile neutropenia with sepsis) occurred in the combination chemotherapy group. Interpretation: Combination chemotherapy with cisplatin plus etoposide plus irinotecan could be considered the standard second-line chemotherapy for selected patients with sensitive relapsed small-cell lung cancer. Funding: National Cancer Center and the Ministry of Health, Labour and Welfare of Japan.